IMPLEMENTASI PEMBELAJARAN BERBASIS TEKS DALAM MATA PELAJARAN BAHASA INDONESIA DI SMP NEGERI GUNUNG TULEH KABUPATEN PASAMAN BARAT - Akbar, Akbar; Atmazaki, Atmazaki; Basri, Irfani (Universitas Negeri Padang, 2018)
ABSTRACTÂ The purpose of this study is to describe 1) the achievement of text-based Indonesian learning planning in Gunung Tuleh 1 Public Middle School, Mount Tuleh 2 Public Middle School, and Mount Tuleh 3 Public Middle School, 2) the achievement of text-based Indonesian language learning at Mount Tuleh 1 Public Middle School, Gunung Tuleh 2 Public Middle School 2, and Mount Tuleh 3 Public Middle School, and 3) achievement of a text-based assessment of Indonesian learning at Mount Tuleh 1 Public Middle School, Mount Tuleh 2 Public Middle School, and Mount Tuleh 3 Public Middle School. This type of research is qualitative research with descriptive methods. The data in this study are the results of data collection by utilizing the observation, interview, and documentation study guidelines. The techniques used in research are observation, interviews, and documentation. Based on the findings of the researcher and discussion, three things can be concluded. 1) Overall aspects of learning planning have been made well by the Indonesian language teacher Gunung Tuleh Public Middle School in accordance with the syllabus and in accordance with Annex IV of the Minister of Education and Culture Regulation No. 81A of 2013. 2) Overall aspects of the implementation of learning that have been made well by the Indonesian language teacher Gunung Tuleh Public Middle School are mostly in accordance with the four stages of text-based learning. 3) Overall aspects of assessment of learning that have been made well by Indonesian language teachers Gunung Tuleh Public Middle School is mostly in accordance with authentic assessment aspects. Â Kata kunci: implementasi, pembelajaran, berbasis teksÂ